Clinical outcomes of liposomal irinotecan in advanced pancreatic adenocarcinoma patients previously treated with conventional irinotecan-based chemotherapy: a real-world study - Gupta, Amol; De Jesus-Acosta, Ana; Zheng, Lei; Lee, Valerie; Kamel, Ihab; Le, Dung; Pishvaian, Michael; Laheru, Daniel (Frontiers in Oncology, 2023)
The efficacy of combination chemotherapy beyond the first-line setting remains modest in patients with advanced pancreatic adenocarcinoma (PAC). Evidence from recent clinical studies has shown that liposomal irinotecan (nal-IRI) plus 5-fluorouracil (5-FU) and leucovorin (LV) resulted in survival benefits in patients with advanced pancreatic adenocarcinoma (APAC) after progression on gemcitabine-based treatment. However, the survival benefits of nal-IRI in the third and later lines, in which limited options are available, have yet to be extensively studied. Also, some studies have shown conflicting results regarding the impact of prior treatment with conventional IRI on patient outcomes following treatment with nal-IRI. Therefore, this real-world study aimed to evaluate the efficacy and safety of nal-IRI plus 5FU-LV in advanced PAC patients who progressed on conventional IRI-containing regimens. Methods: A retrospective chart review was conducted between November 2016 to December 2022 on 30 patients diagnosed with advanced PAC who completed at least one cycle of nal-IRI plus 5-FU-LV and were previously treated with conventional IRI. Data regarding survival outcomes were retrieved. Results: Thirty patients met the inclusion criteria. Overall, 76.7% of the patients received at least two lines of therapy prior to nal-IRI. The median overall duration of nal-IRI treatment was 2.0 months (IQR: 1.3 -3.9 months). One patient (3.3%) had a partial response, and seven patients (23.3%) had stable disease as their best response. The median progression-free survival (PFS) was 1.9 months (95% CI 1.6 -2.0) and the 6-month PFS rate was 20.0%. The median overall survival (OS) was 5.0 months (95% CI 3.4 -7.0), and the 6month OS rate was 36.7%. An interval between conventional IRI and nal-IRI ≥5.5 months was significantly associated with prolonged OS of 10.2 months (95% CI 3.3 -12.1) versus 4.3 months (95% CI 2.1 -5.9; p =0.003). Ten patients (33.3%) experienced grade 3 adverse events, most commonly nausea, fatigue, diarrhea, and non-neutropenic fever. Conclusion: Nal-IRI plus 5FU/LV had modest survival benefits and an acceptable safety profile in patients with prior conventional IRI. A longer interval between conventional IRI and nal-IRI was associated with increased survival outcomes.